Realizing Good Governance Through the Role of Regional Inspectorates: An Analysis of Stakeholder Perceptions in Brebes Regency - Afwan Abdi Salam; Siti Khumayah; Sri Wulandari (Syntax Literate, 2026)
The realization of good governance in local governments remains a persistent challenge, particularly in ensuring accountability, transparency, and effective internal supervision, as the role of the Regional Inspectorate, as part of the Government Internal Supervisory Apparatus (APIP), is often constrained by structural limitations and diverse stakeholder expectations. This study aims to analyze stakeholder perceptions of the role of the Regional Inspectorate in realizing good governance in Brebes Regency and to identify key obstacles that shape these perceptions. Using a qualitative descriptive approach, data were collected through in-depth, semi-structured interviews, observation, and document analysis involving purposively selected informants from internal government institutions, village administrations, law enforcement agencies, and civil society organizations. The data were analyzed inductively through thematic interpretation and triangulation to ensure credibility and analytical rigor. The findings indicate that stakeholders generally perceive the Regional Inspectorate as undergoing a transformation from a traditional watchdog into a strategic partner that supports accountability, legal compliance, and risk mitigation; however, this perception is not evenly distributed due to constraints such as limited human resources, delays in responding to public complaints, insufficient transparency of supervision results, and structural dependence within the regional bureaucratic hierarchy. In addition, divergent expectations emerge between bureaucratic actors who emphasize preventive guidance and mentoring and civil society actors who prioritize enforcement and sanctioning functions. The study implies that strengthening good governance at the local level requires enhancing the institutional independence of the Regional Inspectorate, optimizing workload and response mechanisms, and improving transparency through the more substantive use of digital information platforms.